2014
DOI: 10.4269/ajtmh.13-0678
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Strongyloides stercoralis Serology in the Management of Patients with Eosinophilia

Abstract: Abstract. Strongyloides stercoralis infection is being increasingly diagnosed out of endemic areas. The aim of this study is to evaluate the usefulness of S. stercoralis serology for the management of probable strongyloidiasis in patients presenting with eosinophilia. Overall, 147 patients were included, 89 (60.5%) patients had a positive S. stercoralis serology. Strongyloides stercoralis larvae were detected only in 15 (10.2%) patients. Twenty-eight patients had human immunodeficiency virus infection. Eighty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 25 publications
(29 reference statements)
4
46
0
Order By: Relevance
“…Another study in Australia on an in-house ELISA based on crude antigen showed, for 65% of the patients, either complete negativization or a consistent decrease in optical density within an average of 9 months after treatment [64]. In another and more recent study in Spain, using the commercially available IVD-ELISA, the same result was obtained for 81% of the treated patients after a 6-month follow-up [63]. Unfortunately, just as for diagnosis, a reference standard for cure is not available.…”
Section: Monitoring Of Cure In Clinical Care and Clinical Trialssupporting
confidence: 53%
See 2 more Smart Citations
“…Another study in Australia on an in-house ELISA based on crude antigen showed, for 65% of the patients, either complete negativization or a consistent decrease in optical density within an average of 9 months after treatment [64]. In another and more recent study in Spain, using the commercially available IVD-ELISA, the same result was obtained for 81% of the treated patients after a 6-month follow-up [63]. Unfortunately, just as for diagnosis, a reference standard for cure is not available.…”
Section: Monitoring Of Cure In Clinical Care and Clinical Trialssupporting
confidence: 53%
“…In low-middle-income countries, just as in developed nations, there is a trend for there to be a decrease in the number of [3,11,13,14,32,33,[35][36][37]43,44,61,63] IFAT, immunofluorescence antibody test; LIPS, luciferase immunoprecipitation system; NPV, negative predictive value; PPV, positive predictive value; STS, sedimentation in tube.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, several authors who have investigated the value of eosinophil count as a marker of cure have reported a significant reduction in mean values after treatment [47,[78][79][80][81]. The fluctuating nature of eosinophil counts in helminth infections, however, poses a challenge.…”
Section: How To Follow Patients After Treatmentmentioning
confidence: 99%
“…Whilst seroconversion does not always take place in patients with strongyloidiasis, serum levels tend to decrease after effective treatment [9,47,[76][77][78][79][80][81].…”
Section: How To Follow Patients After Treatmentmentioning
confidence: 99%